Life Interrupted: The Nature and Consequences of Cryostasis - Malter, Henry (Seminars in Reproductive Medicine, 2018)
Cryopreservation and associated cryostorage has become a well-established technique in both basic and clinical science. When the potentially lethal consequences of freezing itself are ameliorated, existence at cryogenic temperatures seems to be a form of true viable stasis that can persist for long periods of time. Natural cryopreservation and revival after long-term periods in cryostasis is reality in many species. While some evidence exists for imperfections in artificial cryopreservation protocols and storage, these protocols are for the most part successful and compatible with efficient restoration of vitality in a variety of biomaterial after freezing. Clinical protocols in use for cryopreserving and storing gametes and embryos in human-assisted reproduction are similarly well proven and supported by a large body of basic science and clinical outcome data.
Keywords: cryopreservation; vitrification; cryostorage; gametes; embryos